2018
DOI: 10.1016/j.aott.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of a laterally misplaced pedicle screw with a re-directed screw. How much pull-out strength is lost?

Abstract: The results of this study confirm that pullout strength of pedicle screw decreases by approximately 71% when the lateral wall is perforated and decreases 28% after redirection to the accurate position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Pedicle screw pullout strength decreases by up to 71% when the lateral wall is perforated, making accurate screw placement of utmost importance [3]. Robotic guidance with navigation assists surgeons in placing screws more consistently and accurately for posterior fixation of the spine [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedicle screw pullout strength decreases by up to 71% when the lateral wall is perforated, making accurate screw placement of utmost importance [3]. Robotic guidance with navigation assists surgeons in placing screws more consistently and accurately for posterior fixation of the spine [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Originally, screws were inserted via the freehand technique, which presents the risk of misplacement. Misplaced screws are not only biomechanically disadvantageous but also carry an increased risk for neurological deficit, vascular damage, and morbidity [1][2][3]. Advances in imaging and navigation such as fluoroscopic guidance have improved the accuracy of screw placement in the spine, yet significantly increased the amount of radiation exposure to the patient, surgeon, and operating room (OR) staff [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that screw misplacement has unpredictable clinical consequences for the patient. Reoperation or removal of the screw not only increases the patient's financial burden and the pressure on the doctor but also leads to unnecessary waste of medical resources [4]. Therefore, it is very important to enhance the accuracy rate of pedicle screw placement using auxiliary equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the robotic assistance could reduce manual errors and perform repetitive work without fatigue [36]. What is more, the high one-time success rate of pedicle screw placement suggested that the RA technique could not only increase the pullout strength of screws, but also save time for readjustment of the screw position, leading to less damage to the pedicle, facet joint and soft tissue [37,38]. Given that intraoperative screw revision could affect the integrity of screw trajectory, the high one-time success rate of screw insertion was often appreciated due to higher pullout strength and lower risk of internal fixation failure [39,40].…”
Section: Discussionmentioning
confidence: 99%